Associations between T-cell traits and narcolepsy type 1: new insights from a Mendelian randomization study - Chen, Shiqin; Lv, Tian; Li, Zongshan; Pan, Gonghua; Chen, Yiqiao; Zhao, Xingwang; Zhang, Lisan (Frontiers in Neurology, 2024)
BackgroundNarcolepsy type 1 (NT1) is primarily caused by a malfunctioning immune system in which T-cells damage the hypothalamus. To elucidate the causal relationships between biomarkers in T-cells and NT1, we employed Mendelian randomization (MR) analysis.MethodsWe conducted a two-sample MR analysis utilizing genetically predicted T-cell traits to examine their effects on NT1. Genome-wide association study summary data were extracted from studies by Valeria (3,757 participants) for 211 T-cell traits, Ollila (6,073 cases and 84,856 controls) for NT1. The MR analysis was executed at two threshold levels. Inverse variance weighted, Wald ratio, weighted median, and MR-Egger regression methods were used for the MR analysis. Odds ratios (ORs) were calculated, and heterogeneity tests, as well as pleiotropy tests, were conducted.ResultsAfter Bonferroni correction at the significant level (p < 1.18 × 10−4), a higher ratio of naive CD4− CD8− T-cells was identified as a risk factor for NT1 (OR = 10.50; 95% CI: 6.98, 15.90, p = 3.89 ×10−29). Conversely, CD4 on HLA DR+ CD4+ T cells (mean fluorescence intensity, MFI) exhibited a negative correlation with NT1. At nominally significant levels (p < 0.05) for both threshold levels, HVEM (herpesvirus entry mediator) on naive CD8+ T cells (MFI) was suggested as a protective factor for NT1. Additionally, a higher ratio of CD25++ CD45RA− CD4 not regulatory T cells, CD127 on CD45RA− CD4 not regulatory T cells (MFI), CD127 on CD28+ CD4+ T cells (MFI), CD3 on HLA DR+ T cells (MFI), and CD3 on HLA DR+ CD4+ T cells (MFI) were suggested as risk factors for NT1.ConclusionThis study confirmed the causal effects of CD4+ and CD8+ T-cells on NT1 and found several novel T-cell-related characteristics.